2017
DOI: 10.1002/aelm.201700063
|View full text |Cite
|
Sign up to set email alerts
|

Rectification‐Regulated Memristive Characteristics in Electron‐Type CuPc‐Based Element for Electrical Synapse

Abstract: As one novel electronic strategy, the integration of memristive behaviors with rectification has shown its potential application. Herein, based on the interfacial effects of a LiF buffer layer at the anode of an electron‐type CuPc memristor on reconfiguring the device energy levels and redistributing the charge accumulations, a new class of organic memristor with rectifying characteristics is proposed. Memristive behaviors characterized by smooth consecutive changes are obtained, which are illustrated in detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…The resistance of the diode structure is measured at ±1.5 V, as plotted in Figure S16b (Supporting Information). [18,[42][43][44][45][46] Due to the thicker Ir layer as well as smaller pore sizes, the possibility of Cu diffusion in the Ir buffer layer is reduced under a low CC of 10 µA. Our diode characteristics are comparable with the results reported in the literature, as shown in Table S1 (Supporting Information).…”
Section: Figure 2asupporting
confidence: 81%
See 1 more Smart Citation
“…The resistance of the diode structure is measured at ±1.5 V, as plotted in Figure S16b (Supporting Information). [18,[42][43][44][45][46] Due to the thicker Ir layer as well as smaller pore sizes, the possibility of Cu diffusion in the Ir buffer layer is reduced under a low CC of 10 µA. Our diode characteristics are comparable with the results reported in the literature, as shown in Table S1 (Supporting Information).…”
Section: Figure 2asupporting
confidence: 81%
“…During the SET process, the device is programmed at self-compliance mode with a stop voltage of +0.8 V ( Figure S17a, Supporting Information). Wang et al have shown 27 conduction states in the TiN/SiO 2 /TaO x /Pt structure [51] and 15 conduction states in the Al/CuPc/LiF/ITO structure [18] at the SET condition. Afterward, the device is allowed to partially RESET at a stop voltage of −0.6 V ( Figure S17b, Supporting Information).…”
Section: Figure 2amentioning
confidence: 99%
“…Memristive synapses with a similar working mechanism have been realized based on Cu‐doped MoO x /GdO x , Ge 2 Sb 2 Te 5 , Nb 2 O 5 , Bi 2 S 3 , HfO 2 /Al 2 O 3 /Si 3 N 4 , CeO 2 , and CuPc/LiF . An organic memristive synapse based on PEDOT:PSS/graphene quantum dot composite films has also been fabricated .…”
Section: Working Mechanisms Of Memristive Synapsesmentioning
confidence: 99%
“…However, the trans-conductance is gradually increasing when the high-frequency stimulation (HFS) arrives or is gradually decreasing when the low-frequency stimulation (LFS) arrives to the biosynaptic connection [20][21][22] To tackle the above issues, the usage of interface-based resistive switching (RS) devices may be a feasible approach due to their highly repeatable analog redistribution of resistance states, whereas electroforming-free behavior eliminates randomness in the resistance states, which is typically generated in memristors with filament formation and growth [23][24][25] . Metal-oxide Schottky-like contact junctions are part of the family of interface-based RS and represent rectifying diode-like switching characteristics within the important framework of electroforming-free operation, large resistance R ON /R OFF ratio and continuously tunable resistance states, making them the most suitable option for mimicking real biosynaptic behaviors, while keeping scaling requirements down [26][27][28] . The shortage of retention time in these devices, as proved by Hansen et al 29 , can be solved with inserting a specific tunneling barrier at the back of the Schottky-like contact of the device.…”
Section: Introductionmentioning
confidence: 99%